Protection of Micro, Small and Medium Enterprises through Regulations Prohibiting Export and Import Goods (Minister of Trade Regulation Number 40 of 2022 concerning the Context of Thrift Shopping) - Wijaya, Dhea Livia; Hakim, Lukmanul; Hesti, Yulia (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Humans are social creatures, which means that in their lives they cannot be separated from other individuals to fulfill their life needs. One of the needs that every human being needs in their life is the need for clothing or clothing. Clothing or what is known as fashion is currently popular with many people, especially among young people. Some people will look for ways to look fashionable by using branded goods but at affordable prices. One way to do this is by buying used clothes or what is now more familiarly called thrift clothes. The presence of thrifting is now familiar to the fashion-loving community. The purpose of this thrifting research is to find out, understand and analyze legal protection for Micro, Small and Medium Enterprises through Regulations Prohibiting Export and Import Goods Based on Minister of Trade Regulation Number 40 of 2022 concerning the Context of Thrift Shopping and Factors causing the Used Clothing Trade in Indonesia. The methods used include problem approaches, sources and types of data, data collection and processing procedures and data analysis. The results of this research are that there are still many people who are interested in used imported clothes, from teenagers to adults, but most of those who are interested in used imported clothes have minimal income. For people who have pocket money and minimal income, they can buy used imported clothes at low prices. and also on the part of business actors, they only spend a small amount of capital so they can open a business selling used imported clothing, there are still many people who do not know that used imported clothing is prohibited from being distributed, and the lack of firmness from the government can be seen that up to now there are still imported clothes circulating. used, therefore, the Trade Department should communicate with the provincial government to carry out stricter control regarding the import of used clothing entering the Lampung area, especially Bandar Lampung City, where to carry out strict control and supervision of imported goods entering, one of which is by tightening guarding at ports of entry for imported used clothing. The conclusion of this research is that government supervision is carried out on business actors in meeting quality standards for the production of goods or services, the inclusion of labels or standard clauses, as well as after-sales services for goods and services and the responsibility of business actors towards consumers in the implementation of buying and selling used clothing. states that business actors are responsible for providing compensation for damage, pollution and/or losses to consumers resulting from consuming goods and/or services produced or traded.